2012
DOI: 10.1002/etc.2065
|View full text |Cite
|
Sign up to set email alerts
|

Metals and bacteria partitioning to various size particles in Ballona creek storm water runoff

Abstract: Abstract-Many storm water best management practice (BMP) devices function primarily by capturing particulate matter to take advantage of the well-documented association between storm water particles and pollutants. The hydrodynamic separation or settling methods used by most BMP devices are most effective at capturing medium to large particles; however, these may not be the most predominant particles associated with urban runoff. The present study examined particle size distribution in storm water runoff from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
(34 reference statements)
1
22
0
1
Order By: Relevance
“…Suspended solids play an important role in the transport of anthropogenic nutrients and heavy metals in streams (Horowitz et al 2008). The concentration of sediment-bound contaminants varies with particle size, with large amounts attached to the finer particles (Taylor and Owens 2009;Brown et al 2013). Hvitved-Jacobsen et al (1994) found 60-80 % of phosphorus and lead, 50-60 % of nitrogen, and 30-40 % of zinc in road runoff to be associated with particulates.…”
Section: Introductionmentioning
confidence: 99%
“…Suspended solids play an important role in the transport of anthropogenic nutrients and heavy metals in streams (Horowitz et al 2008). The concentration of sediment-bound contaminants varies with particle size, with large amounts attached to the finer particles (Taylor and Owens 2009;Brown et al 2013). Hvitved-Jacobsen et al (1994) found 60-80 % of phosphorus and lead, 50-60 % of nitrogen, and 30-40 % of zinc in road runoff to be associated with particulates.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, the highest concentration of pollutants was in the < 6 \im filter fraction, probably because of the pollutants in the dissolved phase being present in this phase. For this study, copper, nickel and zinc (same metals reported by Brown et al, 2013) have the highest influent concentration in the dissolved phase, which when added to the F2 (0.45-8 |xm) size fraction, gives a concentration higher than the F3 (8-20 |.im) size fraction.…”
Section: Namentioning
confidence: 52%
“…The implication is that, bydrodynamic devices would not be appropriate to reduce the concentration of these pollutants, given that HD units remove only particles above 100 |im. Brown et al (2013) have made the same observation for urban runoff entering a creek in southern California. In their study, the highest concentration of pollutants was in the < 6 \im filter fraction, probably because of the pollutants in the dissolved phase being present in this phase.…”
Section: Namentioning
confidence: 62%
See 1 more Smart Citation
“…Każde z zastosowanych rozwiązań materiałowych dachu może w odmienny sposób wpływać na jakość odprowadzanych wód opadowych. Jednym z istotnych zanieczyszczeń identyfikowanych w spływach są zawiesiny bę-dące nośnikiem innych zanieczyszczeń, w tym jonów metali ciężkich i domieszek mikrobiologicznych (Brown, Stein, Ackerman, Dorsey, Lyon i Carter, 2013). Wyniki badań Vaze'a i Chiewa (2004) wykazały, że transport mikrozanieczyszczeń odbywa się głównie z zawiesinami o średnicach mniejszych od 50 μm.…”
Section: Wprowadzenieunclassified